Social networking sites adoption among entrepreneurial librarians for globalizing startup business operations - Gupta, V.; Rubalcaba, L.; Gupta, C.; Pereira, L. (Library Hi Tech, 2022)
Purpose The purpose of this study is to identify the factors leading to adoption of social networking sites (SNS) by librarians of entrepreneurial libraries to provide support to business community in their market research. Identification of these adoption factors will help to design SNS in the way that led to their seamless diffusion in university libraries, making them capable of providing reliable and useful market knowledge to the business community. Design/methodology/approach To meet the research objectives, this study is based on the technology adoption model (TAM). The survey was conducted with 50 librarians of various universities across Europe, Asia, America, Africa and Australia, sampled through non probabilistic sampling techniques-purposive and snowball sampling. The collected data are analyzed through partial least squares structural equation modeling (PLS-SEM) to estimate the formulated structural equation model using SmartPLS 3.2.9 software version. Findings The results indicate that university librarians have high perception about usefulness and ease of using SNS for meeting their business objectives. The perceived usefulness (PU) is solely based on the prolonged adoption of SNS technology in personal lives of the librarians. The perceived ease of use (PEU) is triggered by the increasing quality of evolving SNS technology, especially user friendliness. The prolonged use of technology, increasing market entry of brands and improving quality of SNS will overcome librarian resistance to use SNS for market research related support to business community. Evolving technologies are more likely to be adopted seamlessly in entrepreneurial libraries. Research limitations/implications This study has implications for librarians, entrepreneurs and technology providers. Librarians should have flexible technology adoption policies in place to keep technology adoption synchronized with changing market conditions. Entrepreneurs should share clear and accurate business needs as well as practicing ethical and lawful business practices. They should also help libraries to gain new skills to make future adoption easier. Technology providers should focus on improving the quality of their technology by increasing their functional utilities, performance and reliability as well as making them more user-friendly. Originality/value This study investigates technology adoption of SNS in libraries from the perspective of providing market research related services to entrepreneurs rather than just digitalizing library services for student users.